If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -5 = -4 + 6 + 6x + -1 Reorder the terms: -5 + 4x = -4 + 6 + 6x + -1 Reorder the terms: -5 + 4x = -4 + 6 + -1 + 6x Combine like terms: -4 + 6 = 2 -5 + 4x = 2 + -1 + 6x Combine like terms: 2 + -1 = 1 -5 + 4x = 1 + 6x Solving -5 + 4x = 1 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -5 + 4x + -6x = 1 + 6x + -6x Combine like terms: 4x + -6x = -2x -5 + -2x = 1 + 6x + -6x Combine like terms: 6x + -6x = 0 -5 + -2x = 1 + 0 -5 + -2x = 1 Add '5' to each side of the equation. -5 + 5 + -2x = 1 + 5 Combine like terms: -5 + 5 = 0 0 + -2x = 1 + 5 -2x = 1 + 5 Combine like terms: 1 + 5 = 6 -2x = 6 Divide each side by '-2'. x = -3 Simplifying x = -3
| 2(12b+7)+9b-1=180-9b-1 | | Y+20=4y-15 | | -2x+12+3x=2+x+10 | | 5-7(2-x)=31-4(x-5) | | 6(x-2)-(x+2)=3x-18 | | 5(x+5)-20=0 | | 123=5x+6(2x-5) | | -2(x-2)-4x=3(x+10)-9x | | 5x-8c=-6 | | -20=8x+2x | | 1-5n+5n-2=1+n-6 | | 7[3-4(x-1)]+6[(2x+7)+-8]=17x-333 | | 4(2w-5)=3w-13 | | 3/8x+16=19 | | 5+2(x)=3(x) | | -4(t-3)=5(-2t+4) | | -6h+3=21 | | -8(4+9r)=7(r-11r) | | 12-x=8x+4 | | 6*7-8=7 | | 8(x-2)=8x | | 2x-2=5x+8 | | 12x+17=13x+1 | | -7x-9=-23 | | w^2-7w-110=0 | | -12+3/4x=3 | | 4n+14=6n | | 5g+4y(-5+3g)=16g | | 9x+11=-1x-5 | | 12(x+2)=2(6x-4)+32 | | 7(2c-5)=25 | | -7392(18x-172)=0 |